The nutritional content and physical characteristics of sago starch and oyster mushrooms as potential functional food ingredients - Rahmawati Rahmawati; Damayanthi Evy; Palupi Eny (BIO Web of Conferences)
The integration of sago starch and oyster mushrooms in food product development remains underexplored. Storage life can be enhanced by processing them into flour. This preliminary study seeks to evaluate the nutritional content and physical characteristics of both food materials. The research utilized proximate analysis and presented descriptive findings based on the average nutrient composition and physical attributes, analyzed in two repetitions. Proximate analysis encompassed protein content, moisture level, ash content, crude fat, carbohydrate content (by difference), and crude fiber. Additionally, this study examined phenolic compounds in oyster mushrooms and resistant starch in sago starch. Physical characterization involved analyzing pasting profiles and color properties of both foods. The results indicate that sago starch contains a notable amount of resistant starch (11.17 g), while oyster mushrooms are rich in crude fiber (12.86%) and phenolics (360.8 mg), with relatively low lipid content (5.81%). All nutrient compositions were analyzed per 100 g on a dry basis. Color and pasting profile tests suggest that white sago starch outperforms oyster mushrooms in these aspects. Despite their differences, both hold promising potential as ingredients for functional food innovations.